Al-Mawardi dan Konsep Kenegaraan dalam Islam - Rashda Diana (TSAQAFAH, 2017)
Al-Mawardi was known as the first Moslem thinker of political theory in 11th century AD, five centuries before westerc scholars found their polical concept. Al-Mawardi’s concept of nation put religion in the centre of legitimacy source for political reality. He tried to compromise the political reality with the ideal of politics based on the law of religion and to make the religion as a justification way for political appropriateness. He said that leadership of nation would be an instrument to transmit prophetic mission in order to maintain the religion and to control the world. Meanwhile, al-Mawardi preferred institutional approach to manage a nation. He intensified the institutional function maximally and stabilized nation’s structure. His idea is surely interesting which is used by modern society today. They call it by social contract theory which means to make relationship between Ahl al-Ikhtiyâr dan Ahl al-Imâmah, that led rights and obligation to each others. If the khalîfah or the imâm wants to be obeyed by his people and asking their loyalty, he has to fulfil his duties such as protecting them and managing their concerns with full responsibility. Therefore, al-Mawardi is one of Moslem thinker of Islamic politics in the medieval who considers that the head of nation could be or changed if he does not have capability anymore to fulfil his duty. Then, the author of this article conclude that al-Mawardi’s theory could be an antithesis of the failed democracy theory.